The Impact of Audit Firm Size on Audit Quality - An Empirical Study of The Vietnamese Stock Market - Thi Giang Tan Tran; Quoc Thuan Pham; Thi Thu Phuong Tran; Thi Thao Hien Bui (SAGE Open)
This research endeavors to investigate the impact of audit firm size on audit quality in Vietnam- a developing country with the expectation of improving audit quality to eliminate financial statement fraud that has been increasing in recent years. Using data from 762 companies listed on HOSE and HNX from 2016 to 2019 and audit quality is proxied by discretionary accruals, this research uses the panel data regression method with POLS, FEM, and REM and then select the appropriate model. The results reveal that discretionary accruals in companies audited by Big4 are lower than in non-Big4 companies. This research significantly contributes to the academic literature on audit quality policies by offering valuable insights into three key aspects. Firstly, it sheds light on the relationship between audit firm size and audit quality within the Vietnamese context, enriching the ongoing scholarly debate with specific empirical evidence. Secondly, the study provides essential evidence to aid government policymakers in formulating relevant policies concerning the approval conditions for audits of public interest entities. Lastly, the research advances the global discussion on audit quality by offering valuable insights that can inform regulatory authorities and policymakers worldwide. In sum, this research paper presents a comprehensive and scholarly approach to proposing policies aimed at enhancing audit quality, making a multifaceted contribution to the field’s ongoing discussions and debates.